2017
DOI: 10.1021/acs.iecr.6b04066
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework UiO-66 as an Efficient Adsorbent for Boron Removal from Aqueous Solution

Abstract: Water-stable metal−organic framework (MOF) UiO-66 was studied in boron removal from water for the first time. XRD, SEM, nitrogen adsorption/desorption isotherms, and thermogravimetric analysis (TG) were employed to confirm the structure. The boron adsorption kinetics, isotherms, thermodynamics, mechanism, and recycling on UiO-66 were further investigated in batch adsorption process. UiO-66 exhibits great adsorption performance of 10.59 mmol• g −1 at 45 °C, and the adsorption process reaches equilibrium rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Notably, PAF‐1‐NMDG and P2‐NMDG also exhibit high saturation capacities relative to other polymeric boron‐selective adsorbents (see Table S4, Supporting Information). Recently, some inorganic materials such as nitrogen‐doped graphene oxide and metal–organic frameworks have also been shown to exhibit impressive boron capacities—as high as 10.6 mmol g −1 (at 45 °C) for the metal–organic framework UiO‐66. However, these materials undergo significant reductions in boron adsorption capacity after a few regeneration cycles, casting doubt on their long‐term performance.…”
Section: Pseudo‐second‐order Rate Model Parameters For Experiments Pementioning
confidence: 99%
“…Notably, PAF‐1‐NMDG and P2‐NMDG also exhibit high saturation capacities relative to other polymeric boron‐selective adsorbents (see Table S4, Supporting Information). Recently, some inorganic materials such as nitrogen‐doped graphene oxide and metal–organic frameworks have also been shown to exhibit impressive boron capacities—as high as 10.6 mmol g −1 (at 45 °C) for the metal–organic framework UiO‐66. However, these materials undergo significant reductions in boron adsorption capacity after a few regeneration cycles, casting doubt on their long‐term performance.…”
Section: Pseudo‐second‐order Rate Model Parameters For Experiments Pementioning
confidence: 99%
“…In this study,a saproof of concept, we focused on Zrbased UiO-66 type MOF,which undergoes sol-gel transition by self-assembly of Zr clusters and terephthalic acid. [11,22,23] TheM OF UiO-66, with the formula [Zr 6 O 4 (OH) 4 (bdc) 6 ] (bdc = 1,4-benzenedicarboxylate), is one of the most important MOFs owing to its high thermal, chemical, and mechanical stabilities, [24,25] and has been increasingly studied for av ariety of applications for example,c atalyst, [26,27] catalyst support, [28,29] adsorbent, [30] gas storage medium, [11] and liquid or gas separation medium. [31,32] We used 2-aminoterephthalic acid (BDC-NH 2 )a so rganic linker to obtain UiO-66-NH 2 because of its good solubility in solvents such as N,Ndimethylformamide (DMF).…”
Section: Introductionmentioning
confidence: 99%
“…For contact time studies, 0.1 g of adsorbent was added to 50 mL of a borate ion solution (100 mg/L at pH 10). The suspension was shaken at 100 rpm for 1, 3,5,8,12,16,20,24,36, and 48 h at 25°C. The effect of pH on adsorption was tested by adding 0.1 g of adsorbent to a borate ion solution (50 mL) at 1, 10, 25, 50, 75, and 100 mg/L (pH = 6, 10, and 12).…”
Section: Effect Of Contact Time and Ph On The Adsorption Of Borate Ionsmentioning
confidence: 99%
“…1,2) Boron is one of the most important micro-nutrients for humans, animals, and plants, used to promote the transport and metabolism of carbohydrates, for the synthesis of hemicellulose and related cell wall material, in cell growth and division, to build chloroplast structure, and in the formation of basal grains. [3][4][5] However, previous studies have reported that the ingestion of large amounts of boron can affect the central nervous system and the reproductive system in humans. 6,7) Therefore the WHO limited the maximum boron concentration in drinking water to 2.4 ppm in 2011, while some countries set a more stringent standard.…”
Section: Introductionmentioning
confidence: 99%